Temperature–time relationships and their implications for thermal history and modelling of silica diagenesis in deep-sea sediments - Varkouhi, S; Tosca, NJ; Cartwright, JA (Elsevier, 2021)
67 Ocean Drilling Program and Deep Sea Drilling Project sites were investigated to determine the relationship between temperature and time for silica diagenesis. The selected sites cover a variety of settings where the opal-A to opal-CT transition zone lies in Cenozoic sediments. The opal-A to opal-CT transition leads to abrupt changes in the sediment petrophysics which are used to identify the diagenetic interval at the study sites. This transition zone is a thin interval ranging in thickness from 10 to 40 m. Controls on transition zone thickness are analysed and temperature was found to be the fundamental driver. This study extends “the time–temperature stability field of Hein et al. (1978)” for the onset of opal-CT precipitation more generally. Active silica diagenesis persists over a long period of time (>35 m.y.) at low temperatures (<30 °C), within 3 m.y. at moderate temperatures (35–55 °C), and much more rapidly at high temperatures (>55 °C) regardless of burial depth. Geothermal gradients and sediment accumulation rates are the principal controls of the rate of silica diagenesis transformation. Sites 794 and 795 in the Japan Sea, as typical cases of deep-sea boreholes capturing active transitions, were selected for further understanding the temperature–time control on silica diagenesis. The reconstructed thermal evolution of sediments from these representative sites demonstrates that the rapid increase in temperatures from the Late Miocene onwards occurred in response to high accumulation rates in the opal-A interval. The higher burial temperatures achieved for the opal-A sediment under higher sedimentation rates and a steeper thermal gradient led to an earlier transition at Site 795 (~5 m.y.) as compared to Site 794 (~8 m.y.). Kinetic-based models are formulated to illustrate the time–temperature dependence of biogenic silica diagenesis. One of the main findings based on this model is that although opal-CT precipitation reaches its peak levels across the transition zone at 8 and 5 m.y. after initial deposition of opal-A at Sites 794 and 795, respectively, the transformation is not completed until 14 m.y. at Site 794 and ca. 9.5 m.y. at Site 795 after initial sedimentation. Given the temperature and elapsed time, the model allows the transformation state of opal-containing sediments to be successfully predicted at any depth in these two sites.